An interesting case of spindle cell sarcoma of elbow - Aboosalih, Sana; Kamal, V. Shruthi; Venkata Mahipathy, Surya Rao Rao; Azhisoor Chandrasekhar, Senthil Kumar; Krishnamurthy Mahendra, Balu; Prasath Jayachandiran, Anand; Sundaramurthy, Narayanamurthy (International Surgery Journal, 2020)
Spindle cell sarcomas are a group of aggressive malignant soft tissue tumors with a diverse clinical presentation. A 32 years old woman presented with a recurrent nerve sheath tumour, involving flexor carpi ulnaris and a portion of ulnar nerve. Wide local excision of the tumour was done creating a 4 cm gap defect in the ulnar nerve. Distal nerve transfer and Guyon’s canal release was done and anterior transposition of ulnar nerve to distal motor branch of ulnar nerve end to side (ETS) supercharge was done preserving motor function to the little and ring finger. Achieving negative surgical margins in primary soft tissue sarcoma is a critical for local disease control. The anatomical and functional compromise that can occur while giving adequate clearance margin for the tumor can be overcome by microsurgical techniques and neuroanastomosis with positive outcomes like preservation of function and better prognosis.